Morphological evidence of collateral sprouting of intact afferent and motor axons of the rat ulnar nerve demonstrated by one type of tracer molecule - Kubek, T; Kýr, M; Haninec, P; Sámal, F; Dubový, Petr (Annals of anatomy, 2004)
In our experimental paradigm we sutured the distal stump of a transected musculocutaneous nerve to an intact ulnar nerve of the rat in an end-to-side fashion. We demonstrated the formation of collateral sprouts from intact afferent and motor axons by application of one type of molecule conjugated by two different fluorophores (Fluoro-Ruby and Fluoro-Emerald). Fluoro-Ruby and Fluoro-Emerald were applied distal to end-to-side suture into fresh cut ends of the ulnar and musculocutaneous nerves, respectively. Formation of collateral sprouts was evidenced by findings of mixed (a yellow to orange color) fluorescence labeling of spinal motoneurons and dorsal root ganglia neurons. Colocalization of two different tracers retrogradely transported to the neurons was verified by the individual green and red fluorescence profiles analyzed by means of the computer-assisted image-analyzing system. Our results unequivocally demonstrate that a nerve stump attached to an intact nerve can induce collateral sprouting of both afferent and motor axons.
Keywords: Animals; kosterní svaly; Motor Neurons; Fluorescent Dyes; Afferent Pathways; Rats, Wistar; axony; aferentní nervové dráhy; Muscle, Skeletal; fluorescenční barviva; počítačové zpracování obrazu; motorické neurony; krysa rodu Rattus; Ulnar Nerve; Axonal Transport; zvířata; axonální transport; Rats; nervus ulnaris; Image Processing, Computer-Assisted; potkani Wistar; Axons